2023
DOI: 10.1253/circj.cj-22-0837
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the OPTIVUS-Complex PCI Multivessel Cohort With the Historical CREDO-Kyoto Registry Cohort-3

Abstract: Background: There is a paucity of data on the effect of optimal intravascular ultrasound (IVUS)-guided percutaneous coronary intervention (PCI) compared with standard PCI or coronary artery bypass grafting (CABG) in patients with multivessel disease. Methods and Results:The OPTIVUS-Complex PCI study multivessel cohort was a prospective multicenter single-arm study enrolling 1,021 patients undergoing multivessel PCI including the left anterior descending coronary artery using IVUS aiming to meet the prespecifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…23) . The OPTIVUS-Complex PCI study multivessel cohort also suggested that optimal IVUS-guided PCI was associated with superior clinical outcomes at one year compared with historical CABG controls in the CREDO-Kyoto registry cohort-3 24) .…”
Section: Ivus-guided Pci Vs Angiography-guided Pcimentioning
confidence: 98%
“…23) . The OPTIVUS-Complex PCI study multivessel cohort also suggested that optimal IVUS-guided PCI was associated with superior clinical outcomes at one year compared with historical CABG controls in the CREDO-Kyoto registry cohort-3 24) .…”
Section: Ivus-guided Pci Vs Angiography-guided Pcimentioning
confidence: 98%
“…Recently, the OPTIVUS-Complex PCI study, a prospective, multi-center registry in Japan demonstrated that IVUS-guided PCI aiming to meet the prespecified OPTI-VUS criteria for optimal stent expansion (minimum stent area > distal reference lumen area [stent length ≥ 28 mm], and minimum stent area > 0.8 × average reference lumen area [stent length < 28 mm]) in patients with multi-vessel disease resulted in low target lesion revascularization rates of around 2% at 1 year at patient and lesion levels [56][57][58].…”
Section: Clinical Evidencementioning
confidence: 99%
“…The cumulative incidence of DAPT discontinuation was only 22.6% at 90 days and 68.8% at 1 year, although these were much higher than in the CREDO-Kyoto registry cohort-3, which was a real-world observational study conducted between 2011 and 2013 (3.3% at 90 days, and 18.9% at 1 year). 8 The enrollment into the present study started in March 2019, when the STOPDAPT-2 trial results were released suggesting the safety and efficacy of 1-month DAPT followed by clopidogrel monotherapy after PCI using drug-eluting stents. 2 The Japanese guideline on antithrombotic therapy after PCI was revised in March 2020 to recommend 1-3 months of DAPT after PCI in patients with HBR or low thrombotic risk.…”
Section: Follow-up Cagmentioning
confidence: 99%
“…The design, patient enrollment, and main results at 1 year were previously reported in detail. 7, 8 Written informed consent was provided from real-world DAPT strategies and the effect of shorter DAPT relative to longer DAPT after multivessel PCI. The OPTIVUS-Complex PCI (Optimal Intravascular Ultrasound Guided Complex Percutaneous Coronary Intervention) multivessel cohort was a prospective multicenter single-arm study enrolling patients who underwent IVUS-guided multivessel PCI with a target of prespecified criteria for optimal stent implantation.…”
mentioning
confidence: 99%